Jakarta F&B Merchants’ Adoption of the E-Payment Gateway System - Chandra, Elita Jessamine; Pradipta, Andamar (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2022)
With the increase of various e-payment service providers, Foods and Beverages (F&B) merchants in Jakarta, especially Small and Medium-Sized Enterprises (SMEs), are encouraged to adopt e-payment systems for their businesses. However, the adoption is still considered low compared to the number of SMEs in the F&B industry in Jakarta. This paper acts as a preliminary study and uses the technology acceptance model on F&B SMEs in Jakarta to analyze the descriptive statistics of 31 respondents in the five cities of Jakarta. The results include the reliability and validity of the instrument, the descriptive statistics measure of frequency, central tendency, and dispersion of variation.